SOCIO-ECONOMIC IMPACT OF GOVERNMENT POLICIES IN THE AGRICULTURAL SECTOR: A CASE STUDY OF CASSAVA PRICE POLICIES IN LAMPUNG - Ardiati, Dede; Buntoro, Fuad; Asriani, Asriani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Cassava is a strategic commodity in Lampung Province that plays an important role in food security and the local economy. Data from Statistics Indonesia in 2024 shows an improving trend in poverty reduction. With 941,230 people compared to 970,670 people in March 2023, this shows that if managed properly, the agricultural sector can reduce poverty levels. However, the oligopsonistic market structure puts farmers in a weak bargaining position. To overcome this, the Lampung Provincial Government issued Governor's Instruction No. 2 of 2025, which sets a reference price of IDR 1,350/kg with a maximum discount of 30%. This study aims to analyze the socioeconomic impact of this pricing policy and its effectiveness for farmers. The research method used is a literature study by examining data from academic journals, BPS reports, and other publications, as well as interviews with selected farmers as respondents. The data is analyzed qualitatively using a descriptive-analytical approach to see the suitability between the policy objectives and the reality in the field. The results of the study show that pricing policies provide little protection for farmers through guaranteed base prices and more secure market access. However, rafaksi practices that are not always transparent, weak supervision, and low productivity remain major obstacles. This study also found that factory closures occurred due to economic pressures and market uncertainty, lax import policies, and weak coordination between the central and regional governments in managing trade. This study confirms that the cassava pricing policy in Lampung serves as an important first step in reducing farmers' vulnerability, but it is not enough to achieve sustainability. Updates to pricing, increased productivity, and institutional support are needed to ensure the sustainable welfare of farmers.